Movências e espaços migratórios goianos no romance "O caminho de Trombas", de José Godoy Garcia - Campos, Ionice Barbosa de (2020)
This thesis aims to analyze the novel O caminho de Trombas (1966), by José Godoy Garcia, turning to aspects of migration as a process that interferes in the construction of displaced subjects. The field and the city, represented, respectively, by São Domingos’ farm and the city of Goiânia are the two most characteristic spaces and through which migrant workers pass, strong and emblematic characters who, in their crowd, seek a place idealized: Trombas, in order to establish themselves. In a very troubled socio-historical-political period such as that of the 1940s and 1960s in Goiás, the narrative is set and is also the context of the plot of the work under analysis. Therefore, our reading will be biased by a perspective that aims to identify the historical and social aspects in the work, as well as the consequent (trans)formation of identities arising from the relationship between the subjects in the migratory process. To this end, we bring authors such as Raymond Williams, Justino, Hall, Candido, Silva, Said, among others who bring to light discussions about migration and literature, identity and culture, otherness and subordination, field and city, diaspora, space in the narrative. We understand, at the end of the research, that migration contributes to the relations of otherness, as well as to the formation of man and his position before what is imposed on him. In addition, we classify Godoy Garcia's work as one of the most important publications produced in Goiás, in the sense that, even on the sidelines, it contributes both to the literary of Goiás and to the history of national literature.